Peran Satlantas dan Pengendara dalam Mengatasi Kemacetan di Jalan Sisingamanga Raja dengan Mengedepankan Sikap Toleransi - Purwadinata, Zweily; Fitri, Valen Asira; Febrian, Maulana; Azim, ZulFadli; Umairoh, Aisiyah Ni’mah; Syahputri, Nadya; Silangit, Harfinsyah Fachrezy; Alhadi, M. Sabiq; Nasution, Saskia Nabila; Haidir, Haidir (UNIVERSITAS SERAMBI MEKKAH, 2025)
Traffic congestion in the region is a complex problem influenced by several variables, including a large number of vehicles, poor infrastructure, and irresponsible drivers, and Satlantas plays an important role in traffic control and regulation. However, a number of challenges still affect Satlantas' ability to reduce traffic congestion, including a lack of funding, poor coordination, and a lack of public understanding of the importance of maintaining traffic order. Furthermore, one of the most important factors affecting traffic conditions is driver behavior. To improve traffic conditions, tolerance, mutual respect, and an understanding of mutual safety are required. However, many drivers are still not aware of this. Fourth, solving traffic problems requires cooperation between the community and the Traffic Police. Congestion reduction initiatives will be more successful if all parties work together and support each other.